Modelo fuzzy estimando tempo de internação por doenças cardiovasculares - Coutinho, Karine Mayara Vieira; Rizol, Paloma Maria Silva Rocha; Nascimento, Luiz Fernando Costa; Medeiros, Andréa Paula Peneluppi De (ABRASCO - Associação Brasileira de Saúde Coletiva, 2015)
Abstract A fuzzy linguistic model based on the Mamdani method with input variables, particulate matter, sulfur dioxide, temperature and wind obtained from CETESB with two membership functions each was built to predict the average hospitalization time due to cardiovascular diseases related to exposure to air pollutants in São José dos Campos in the State of São Paulo in 2009. The output variable is the average length of hospitalization obtained from DATASUS with six membership functions. The average time given by the model was compared to actual data using lags of 0 to 4 days. This model was built using the Matlab v. 7.5 fuzzy toolbox. Its accuracy was assessed with the ROC curve. Hospitalizations with a mean time of 7.9 days (SD = 4.9) were recorded in 1119 cases. The data provided revealed a significant correlation with the actual data according to the lags of 0 to 4 days. The pollutant that showed the greatest accuracy was sulfur dioxide. This model can be used as the basis of a specialized system to assist the city health authority in assessing the risk of hospitalizations due to air pollutants.

Resumo Para prever o tempo médio de internações por doenças cardiovasculares relacionadas à exposição de poluentes do ar em São José dos Campos (SP), em 2009, foi construído um modelo linguístico fuzzy, baseado no método de Mamdani, com variáveis de entrada: material particulado, dióxido de enxofre, temperatura e vento, obtidos da CETESB, com duas funções de pertinência cada. A variável de saída é o tempo médio de internações, obtido do Datasus, com seis funções de pertinência. O tempo médio fornecido pelo modelo foi comparado aos dados reais segundo defasagens de 0 a 4 dias. Este modelo foi construído no toolbox fuzzy do Matlab v. 7.5. Sua acurácia foi avaliada pela curva ROC. Foram registradas 1119 internações com o tempo médio de 7,9 dias (dp = 4,9). Os dados fornecidos mostraram significativa correlação com os dados reais, segundo as defasagens de 0 a 4 dias. O poluente que mostrou melhor acurácia foi o dióxido de enxofre. Este modelo pode ser utilizado como base de sistema especialista, que pode auxiliar o gestor municipal na avaliação do risco de internações em função dos poluentes do ar.
Fuzzy model approach for estimating time of hospitalization due to cardiovascular diseases
Keywords: Fuzzy logic; Air pollutants; Cardiovascular diseases; Sulfur dioxide; Particulate matter; Lógica fuzzy; Poluentes do ar; Doenças cardiovasculares; Dióxido de enxofre; Material particulado